110th anniversary of the outstanding scientist corresponding member of the Academy of Sciences of the Republic of Kazakhstan ENGVAN INSUGOVICH KIM (1911–1994) - Jenaliyev, M.T. (Bulletin of the Karaganda University. Mathematics Series, 2022)
In November 2021 it was the 110th anniversary of the birth of the outstanding Scientist, Doctor of Science in Physics and Mathematics, Professor E.I. Kim, who made a significant contribution to the development of mathematical science in Kazakhstan, created a school for the study of equations of mathematical physics and raised many students who continue his research.